IBM z16 technical introduction - White, Bill (Telecommunications engineer); Lascu, Octavian; Palacio, Ewerson; Ertl, Makus; Houlbjerg, Jannie; Kamga, Hervey; Laumay, Gerard; Martinksi, Slav; Nakajima, Kazuhiro; Raave, Martijn; Schouten, Paul; Shugol, Anna; et al. (IBM redbooks., 2022)
This IBM® Redbooks® publication introduces the latest member of the IBM Z® platform that is built with the IBM Telum processor: the IBM z16 server. The IBM Z platform is recognized for its security, resiliency, performance, and scale. It is relied on for mission-critical workloads and as an essential element of hybrid cloud infrastructures. The IBM z16 server adds capabilities and value with innovative technologies that are needed to accelerate the digital transformation journey. This book explains how the IBM z16 server uses innovations and traditional IBM Z strengths to satisfy the growing demand for cloud, analytics, and a more flexible infrastructure. With the IBM z16 servers as the base, applications can run in a trusted, reliable, and secure environment that improves operations and lessens business risk.